Enhancement of An Algorithm To Extract Text-Lines From Images For Blind And Visually Impaired Persons Through Parallel Approach. - Jivane, Niketan; Jivane, Supriya; Rajkumar, S; Marimuthu, K (International Journal of Computer Sciences and Engineering, 2025)
Applications with Text Extraction form image or videos are boon for people with blindness to assist them in their day to day life. The emergence of high resolution cameras on mobile devices can be used to extract text-line. The literature presents that there are a number of algorithms that have been proposed for the extraction of text-lines from images. The Computation cost of these methods is very high and failed to address the challenging problem in text extraction due to the scale and orientation of the characters. In this paper, we propose a method to enhance an algorithm for quick retrieval of text from image documents using Parallel Matlab. Finally, it demonstrates the improvement in extracting text lines from the existing algorithm through results.